Technological data of the industrial sausages production - ΠΑΠΑΔΟΠΟΥΛΟΣ, ΧΡΥΣΑΝΘΟΣ TP. (Journal of the Hellenic Veterinary Medical Society, 2019)
Sausages are a food that is prepared from comminuted and seasoned meat and is usually formed into a symetrical shape. The stages of the manufacturing sausages production can be estimated as follows: a) The choise of the sausage ingredients. In this chapter we examined the animal tissues and mainly the lean skeletal meats, the moisture, the proteins, the fat, the salt, the sweetening agents, the seasoning and the extenders that are non meat materials and are classified as binders animal or vegetable origin, as fillers, flour processed and as stabilizers, non meat extenders. b) The sausage emulsion , that is a two-phase system, consisting from salt-soluble meat mainly proteins and fat tissue. c) The color development in cooked sausages, through a process generally used with nitrite salts mainly in the curing formula. d) Filling of the comminuted meat in natural or manufactured casings, or in metal molds.